The Influence of Sustainable Marketing Innovation, Corporate Social Responsibility, and Consumer Preferences on Purchasing Decisions in Jakarta - Frans Sudirjo; Ilham Akbar Bunyamin; Slamet Sutrisno (West Science Social and Humanities Studies, 2024)
This research investigates the impact of sustainable marketing innovation, corporate social responsibility (CSR), and consumer preferences on purchasing decisions among consumers in Jakarta, Indonesia. Through a quantitative approach, data were collected from 172 respondents and analyzed using structural equation modeling (SEM). The results indicate significant positive relationships between sustainable marketing innovation, CSR, consumer preferences, and purchasing decisions. Specifically, sustainable marketing innovation and CSR were found to positively influence consumer preferences and subsequently impact purchasing decisions. These findings underscore the importance of sustainability and social responsibility in shaping consumer behavior and highlight the need for businesses to align their marketing strategies with consumer values to drive positive purchasing behavior. The study contributes to the existing literature on sustainable consumption and provides practical insights for businesses operating in emerging markets like Jakarta.